Lipid composition of the isolated rat intestinal microvillus membrane - Forstner, G. G. (1968)
1. Rat intestinal microvillus plasma membranes were prepared from previously isolated brush borders and the lipid composition was analysed. 2. The molar ratio of cholesterol to phospholipid was greatest in the membranes and closely resembled that reported for myelin. 3. Unesterified cholesterol was the major neutral lipid. However, 30% of the neutral lipid fraction was accounted for by glycerides and fatty acid. 4. Five phospholipid components were identified and measured, including phosphatidylethanolamine, phosphatidylcholine, phosphatidylserine, sphingomyelin and lysophosphatidylcholine. Though phosphatidylethanolamine was the chief phospholipid, no plasmalogen was detected. 5. In contrast with other plasma membranes in the rat, the polar lipids of the microvillus membrane were rich in glycolipid. The cholesterol:polar lipid (phospholipid+glycolipid) ratio was about 1:3 for the microvillus membrane. Published data suggest that this ratio resembles that of the liver plasma membrane more closely than myelin or the erythrocyte membrane. 6. The fatty acid composition of membrane lipids was altered markedly by a single feeding of safflower oil. Membrane polar lipids did not contain significantly more saturated fatty acids than cellular polar lipids. Differences in the proportion of some fatty acids in membrane and cellular glycerides were noted. These differences may reflect the presence of specific membrane glycerides.